Design and experimental study on precooled MR JT cryocooler for LNG recondensation purposes. (October 2022) - Rogala, Zbigniew; Siemasz, Rafał; Baran, Błażej; Kwiatkowski, Adrian
Abstract: The paper presents a preliminary experimental study of the precooled MR JT cryocooler, which was designed for LNG recondensation and potentially liquefaction purposes. The paper also includes the most vital aspects of the design: compressor selection and limitations, selection and size of expansion devices, effect of MR composition on the stability of the load temperature, and minimum approach during recuperation. In addition, a detailed description of the features of the test stand is provided. A series of experimental tests has been performed with varied heat load, suction pressure, discharge pressure, and precooling temperature. The cryocooler provided cooling power of 270 W at a temperature of −158 °C, which is the largest MR JT cryocooler reported in the literature. Experiments indicate an optimum precooling temperature similar to that derived from the theoretical study (approximately −35 °C). Highlights: Precooled MR JT cryocooler for LNG recondensation purposes has been designed. The performance of the cryocooler has been experimentally evaluated. Designed and tested cryocooler provided cooling power of 270 W at a temperature of −158 °C. Optimum precooling temperature of MR is about −35 °C.